EXAMINING DISCURSIVE DEVICES IN PRINT MEDIA TEXTS ON HERDER-FARMER CLASHES: A CRITICAL PRAGMATIC APPROACH - USMAN, Mohammed Alhaji (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
This study investigates discursive devices explored by Nigerian newspaper reporters on herder-farmer clashes in Nigeria. Seven sampled texts are gathered from The Guardian, Daily Sun and Daily Trust newspapers of 2020 and 2021. The analysis is based on Halliday’s Interpersonal Metafunction theory and Face theory of pragmatics. Findings of the study reveal preponderance of hedges achieved through words and phrases like ‘Gunmen suspected to be Fulani herdsmen allegedly …’, ‘… reportedly’, ‘… said to be …’, etc. deployed for the purpose of politeness, self-protection, threat mitigation and expression of lack of full commitment to the claims in the news reports. Based on this, the author concludes that, while on one hand, the preponderance of hedges in this study implies that the reporters are not eye-witnesses to the incidents of herder-farmer clashes being reported, on the other hand, it constitutes strategy explored by the reporters to save or mitigate the face of the individuals, groups, or interests that might be threatened with the reports in order to avoid worsening the situation. In other words, hedges in this study are signs of politeness, humility, modesty and respect on the part of the reporters.